Silicon-carbon anode materials and their preparation methods, lithium-ion battery anode sheets and lithium-ion batteries

CN122950459APending Publication Date: 2026-10-20LANXI ZHIDE ADVANCED MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611417270.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-14
Publication Date
2026-10-20

AI Technical Summary

Technical Problem

但硅基材料存在致命缺陷:在锂离子嵌脱过程中会产生高达300%的体积膨胀,极易导致活性材料粉化脱落、电极片开裂、活性物质与集流体电接触中断,最终造成电池容量快速衰减、循环寿命大幅缩短,严重制约硅基负极的规模化应用

Benefits of technology

本发明提供的硅碳负极材料,所述硅碳负极材料通过限定微孔率≥10%,保障硅前驱体可充分渗透至多孔碳骨架内部孔道,实现硅在孔壁内表面的均匀成核与限域沉积,避免表面结壳及内部孔隙空置;通过限定限域尺度比Z在0.2<Z<15范围内,使活性硅区域尺寸与孔道尺度形成几何适配,既防止硅以离散颗粒形式分布导致膨胀失控,又避免跨孔桥连引发孔道封堵;通过将化学气相沉积温度控制在380℃~800℃区间,在确保硅前驱体充分裂解的同时,有效抑制硅结晶化及碳骨架脆化,维持无定形硅的各向同性缓冲能力;通过控制硅前驱体沉积转化速率Y<0.1,使化学气相沉积工艺占主导,抑制化学气相渗透效应,从而保持孔隙全程贯通,提升离子与电子传输效率;通过使硅前驱体利用率X(Si)>92%,在保证高硅负载的前提下显著降低原料浪费与尾气处理负担,提升工艺经济性与安全性。上述五项参数协同作用,使该硅碳负极材料兼具高比容量、高首圈库伦效率、低充放电体积膨胀及长循环寿命。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure FT_3
    Figure FT_3
Patent Text Reader

Abstract

This invention provides a silicon-carbon anode material and its preparation method, a lithium-ion battery anode sheet, and a lithium-ion battery, relating to the field of lithium-ion battery technology. The silicon-carbon anode material comprises a porous carbon framework and silicon deposited on the surface of its internal open-pore structure, simultaneously satisfying the following: (a) microporosity ≥ 10%, ensuring sufficient penetration and uniform confined deposition of the silicon precursor; (b) confinement size ratio Z within the range of 0.2 < Z < 15, achieving geometric adaptation between silicon and the pores and suppressing discrete expansion or pore blockage; (c) chemical vapor deposition temperature of 380~800℃, balancing sufficient precursor decomposition and amorphous silicon stability; (d) silicon precursor deposition conversion rate Y < 0.1, ensuring pore connectivity; and (e) silicon precursor utilization rate X(Si) > 92%, achieving high silicon loading and process economy. The above five parameters synergistically endow the material with high specific capacity, high first-cycle coulombic efficiency, low volume expansion, and long cycle life.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of lithium-ion battery technology, and in particular to a silicon-carbon anode material and its preparation method, a lithium-ion battery anode sheet, and a lithium-ion battery. Background Technology

[0002] Lithium-ion batteries, with their advantages of high energy density, long cycle life, no memory effect, and environmental friendliness, have become core energy storage devices in consumer electronics, new energy electric vehicles, and large-scale energy storage power stations. As terminal devices rapidly iterate towards lightweight design, long battery life, and high-rate charging and discharging, the performance limitations of traditional commercial graphite anodes are becoming increasingly apparent. The theoretical specific capacity of graphite anodes is only 372 mAh / g, and the actual industrialized capacity is already close to the theoretical limit, failing to meet the development demands of ultra-high energy density in high-end lithium batteries.

[0003] Elemental silicon boasts advantages such as an ultra-high theoretical specific capacity of 3579 mAh / g, extremely low lithium insertion / extraction potential, abundant reserves, and low cost, making it the most promising next-generation high-capacity anode material for industrialization. However, silicon-based materials have a fatal flaw: during lithium-ion insertion / extraction, they experience volume expansion of up to 300%, which easily leads to the pulverization and shedding of active materials, electrode cracking, and interruption of electrical contact between the active material and the current collector. Ultimately, this results in rapid capacity decay and a significant reduction in cycle life, severely restricting the large-scale application of silicon-based anodes.

[0004] Currently, the mainstream solution in the industry is to prepare silicon-carbon composite materials by combining silicon and carbon materials, utilizing the high conductivity, good mechanical toughness, and porous structure of carbon materials to buffer the volume expansion of silicon. Among them, vapor-deposited silicon-carbon materials, which use porous carbon as a framework and deposit silicon in a confined space within the pores through chemical vapor deposition, have advantages such as confined pore expansion, continuous conductive network, and strong structural stability, and are a key research direction for high-performance silicon-carbon anodes.

[0005] However, existing vapor-deposited silicon-carbon materials still suffer from the following technical defects, failing to achieve a balance between high silicon content and high stability: First, the micropore ratio of the carbon framework is too low, preventing silicon precursors from penetrating deep into the pores and causing them to only pyrolyze and form a shell on the particle surface. This results in extremely low utilization of internal pores, large irreversible capacity in the first cycle, and easy peeling of the surface silicon shell during cycling. Second, improper deposition temperature control leads to insufficient pyrolysis of silicon precursors and low deposition efficiency at low temperatures, while silicon easily crystallizes at high temperatures, losing its isotropic buffering capacity for expansion and damaging the mechanical flexibility of the carbon framework. Third, unreasonable silicon introduction methods result in an excessively high proportion of chemical vapor infiltration processes, which preferentially deposit and block pores at the pore openings, leading to empty internal pores and extremely poor deposition uniformity. Fourth, silicon precursor utilization is generally low, and the silicon loading of the products is insufficient. Most materials have a silicon content of less than 90%, failing to leverage the high capacity advantage of elemental silicon and resulting in limited capacity performance improvement.

[0006] In summary, existing technologies lack a complete parameter coordination system, making it impossible to achieve uniform confined deposition, stable amorphous phase, and good porosity under high silicon load conditions with high silicon precursor utilization (X(Si) > 92%). It is also difficult to achieve high specific capacity, low volume expansion, and long cycle life.

[0007] Therefore, there is an urgent need to develop a high-silicon content vapor-deposited silicon-carbon anode material with controllable structure and excellent performance, as well as its preparation process.

[0008] In view of this, the present invention is hereby proposed. Summary of the Invention

[0009] It should be noted that the testing, calculation, and judgment criteria for the five performance parameters—microporosity, confinement size ratio, chemical vapor deposition temperature, silicon precursor deposition conversion rate, and silicon precursor utilization rate—are as follows: 1. V micro (Microporosity): Parameter definition: refers to the percentage of the total pore volume of the material that is composed of micropores with a pore size of less than 2 nm.

[0010] Standard determination and calculation method: The pore structure of the sample was tested using the 77K nitrogen adsorption method. The total micropore volume and the total pore volume of the material were calculated using the DFT or HK model, and the ratio of the two is the microporosity.

[0011] 2. T (Deposition temperature) Parameter definition: The actual surface temperature of the porous carbon skeleton during chemical vapor deposition.

[0012] Standard measurement and calculation method: Real-time monitoring is performed using thermocouples or infrared thermometers built into the reactor, and the constant temperature during the deposition stage is taken as the test result.

[0013] 3. Y (Deposition conversion rate of silicon precursor gas): Parameter definition: Y = (moles of silicon precursor gas / moles of porous carbon framework) / deposition time. This parameter characterizes the silicon precursor deposition conversion rate per unit mole of porous carbon framework and per unit deposition time, aiming to avoid pore blockage at the process level.

[0014] Standard determination and calculation method: Compare the sample weight gain data before and after the vapor deposition process, and estimate the weight gain based on the total silicon content.

[0015] 4. X (Si) (Silicon precursor utilization): Parameter definition: X(Si) = 100% × (number of moles of silicon in the composite) / (total number of moles of silicon precursor feed). This parameter is used to characterize the degree of utilization of the silicon precursor in the conversion into product silicon.

[0016] Standard determination and calculation method: Thermogravimetric analysis (TGA) was used to determine the mass of silicon in the composite (the temperature was increased from 25°C to 1100°C in air atmosphere until all carbon was burned off and silicon was oxidized to SiO2, and the mass of silicon was calculated according to the formula "mass of silicon = M"). 1100 Calculate ×28 / 60”, where M 1100 (Sample mass at 1100℃). The obtained silicon mass was converted into silicon moles, and combined with the total number of silicon precursor feed moles recorded during the reaction, the result was calculated using the formula X(Si) = 100% × (number of silicon moles in the composite) / (total number of silicon precursor feed moles). The silicon mass fraction of the material can be used as evidence of its composition, calculated from the same set of TGA data.

[0017] 5. Z (Confined Scale Ratio): Parameter definition: The ratio of the average particle size DSi of the active silicon region to the average pore size Dp of the porous carbon framework channels, i.e., Z=D Si / D p This value is a dimensionless parameter used to characterize the geometric fit between the silicon region size and the channel size.

[0018] Standard measurement and calculation method: Statistical analysis of no less than 50 pores was performed using cross-sectional TEM / SEM; the average pore diameter D was determined through image analysis. p The average characteristic dimension D of the active silicon region (including the silicon film on the walls of the vias or the silicon region inside the vias) was determined by EDS surface scanning or aberration-corrected TEM. Si Calculate the ratio Z=D Si / D p It can also be verified using FIB-SEM 3D reconstruction technology.

[0019] Note: All the above parameter tests were conducted using industry-standard testing equipment and methods.

[0020] The primary objective of this invention is to provide a silicon-carbon anode material. This silicon-carbon anode material constructs a confined composite system with stable structure, interconnected channels, and controllable phases under high silicon loading by synergistically limiting five key parameters: microporosity ≥10%, confinement size ratio 0.2 < Z < 15, deposition temperature 380–800℃, silicon precursor deposition conversion rate Y < 0.1, and utilization rate X(Si) > 92%. This results in a material that combines high specific capacity, high first-cycle coulombic efficiency, low charge-discharge volume expansion, and long cycle life.

[0021] The second objective of this invention is to provide a method for preparing silicon-carbon anode materials.

[0022] A third objective of this invention is to provide a lithium-ion battery negative electrode sheet.

[0023] The fourth objective of this invention is to provide a lithium-ion battery.

[0024] In order to achieve the above-mentioned objectives of the present invention, the following technical solution is adopted: This invention provides a silicon-carbon anode material, comprising a porous carbon framework and silicon deposited on the surface of the open-pore structure channels inside the porous carbon framework. The anode material simultaneously satisfies the following parameter conditions: (a) Microporosity (V) mciro ≥10%, where the microporosity refers to the percentage of the volume of micropores with a pore size of less than 2 nm in the total pore volume of the negative electrode material; (b) The bounded scale ratio Z satisfies 0.2 < Z < 15, where Z = D si / D p D Si D represents the average particle size of the active silicon region. p The average pore size of the porous carbon framework channels; (C) The silicon is introduced by a chemical vapor deposition process, and the deposition temperature of the chemical vapor deposition is 380℃~800℃; (d) The silicon precursor deposition conversion rate Y < 0.1, where Y = (moles of silicon precursor raw material gas / moles of porous carbon framework) / deposition time, and the moles of porous carbon framework are calculated in terms of moles of carbon elements; (e) Silicon precursor utilization rate X(Si) > 92%, where X(Si) = 100 × (number of moles of silicon in the composite) / (total number of moles of silicon precursor feed).

[0025] Furthermore, the microporosity (V) mciro The percentage is 40% to 95%; And / or, the preferred value range of Z is 0.5 < Z < 0.8.

[0026] Furthermore, the porous carbon framework has a specific surface area of ​​300~2500m² / g and a total pore volume of 0.3~2.0cm³ / g.

[0027] And / or, the raw materials for preparing the porous carbon framework are selected from one or more of asphalt, resin, coal, biomass, metal-organic framework compounds and their derivatives; And / or, the D50 particle size of the porous carbon framework is 1 μm to 30 μm.

[0028] Furthermore, the silicon is bonded to the inner surface of the pore wall of the porous carbon skeleton in the form of a continuous thin film, and the thin film is located inside the pores of the porous carbon skeleton. And / or, the equivalent thickness of the film is 1 nm to 20 nm.

[0029] Furthermore, the outer surface of the porous carbon skeleton is also covered with a coating layer; And / or, the thickness of the coating layer is 1~50nm; And / or, the coating layer is a carbon coating layer or a non-carbon coating layer, wherein the carbon coating layer is an amorphous carbon layer, a graphitized carbon layer, or a composite layer of both, and the non-carbon coating layer is a silicon oxide, a metal oxide, or a polymer.

[0030] The present invention provides a method for preparing the above-mentioned silicon-carbon anode material, the method comprising the following steps: (A) Provide a porous carbon framework with a microporosity of ≥10%, and then place the porous carbon framework in a closed reactor and introduce a mixture of silicon precursor gas. (B) At a deposition temperature of 380–800 °C, silicon is uniformly deposited in the pores of a porous carbon framework by chemical vapor deposition (CVD) process. The proportion of chemical vapor infiltration process is strictly controlled so that the resulting anode material satisfies Y < 0.1, X(Si) > 92%, and 0.2 < Z < 15.

[0031] Furthermore, in (A), the silicon-containing precursor mixed gas is formed by mixing the silicon-containing precursor with a carrier gas; And / or, the silicon-containing precursor is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; And / or, the carrier gas is an inert gas; And / or, the volume fraction of the silicon-containing precursor in the silicon-containing precursor mixture is 5% to 50%, and the system pressure is 5 to 50 kPa.

[0032] Furthermore, the chemical vapor deposition in (B) is a segmented temperature-controlled deposition: The temperature for the pre-deposition stage is 380~450℃ and the time is 0.2~0.5 h, while the temperature for the main deposition stage is 450~800℃ and the time is 1.0~2.5 h.

[0033] The present invention provides a lithium-ion battery negative electrode sheet, the negative electrode sheet comprising a current collector and a negative electrode active material layer coated on the surface of the current collector, the negative electrode active material layer comprising the above-mentioned silicon-carbon negative electrode material, a binder and an optional conductive agent; And / or, the silicon-carbon anode material accounts for 3% to 100% of the mass of the anode active material layer.

[0034] The present invention provides a lithium-ion battery, which includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is the negative electrode sheet of the lithium-ion battery of the present invention.

[0035] Compared with the prior art, the beneficial effects of the present invention are as follows: The silicon-carbon anode material provided by this invention, by limiting the microporosity to ≥10%, ensures that the silicon precursor can fully penetrate into the internal pores of the porous carbon framework, achieving uniform nucleation and confined deposition of silicon on the inner surface of the pore walls, avoiding surface crusting and internal pore vacancy; by limiting the confinement scale ratio Z to the range of 0.2 < Z < 15, the size of the active silicon region and the pore size are geometrically matched, preventing both uncontrolled expansion caused by silicon distributed in discrete particle form and pore blockage caused by cross-pore bridging; and by controlling the chemical vapor deposition temperature at 38°C... Within the temperature range of 0℃ to 800℃, while ensuring sufficient pyrolysis of the silicon precursor, silicon crystallization and carbon framework embrittlement are effectively suppressed, maintaining the isotropic buffering capacity of amorphous silicon. By controlling the silicon precursor deposition conversion rate Y < 0.1, the chemical vapor deposition process is made dominant, suppressing the chemical vapor infiltration effect, thereby maintaining full pore connectivity and improving ion and electron transport efficiency. By ensuring the silicon precursor utilization rate X(Si) > 92%, raw material waste and tail gas treatment burden are significantly reduced while ensuring high silicon loading, improving process economy and safety. The synergistic effect of the above five parameters enables this silicon-carbon anode material to possess high specific capacity, high first-cycle coulombic efficiency, low charge-discharge volume expansion, and long cycle life.

[0036] The method for preparing silicon-carbon anode materials provided by this invention involves step (A) selecting a porous carbon framework with a microporosity ≥10% and introducing a mixed gas containing silicon precursors to provide necessary permeation channels and nucleation basis for the silicon precursors to penetrate deep into the pores; and step (B) implementing a deposition process dominated by chemical vapor deposition within a precise temperature window of 380–800°C, while strictly controlling the proportion of chemical vapor permeation. This simultaneously achieves efficient pyrolysis of the silicon precursors, uniform and continuous silicon film formation on the inner surface of the pore walls, and the synergistic achievement of high silicon precursor utilization and confinement size ratio. Thus, from the source of the process, the resulting silicon-carbon anode material is guaranteed to have comprehensive performance characteristics such as high silicon loading, low volume expansion, high first-cycle coulombic efficiency, and long-cycle stability.

[0037] The lithium-ion battery negative electrode sheet provided by the present invention uses the aforementioned silicon-carbon negative electrode material as the negative electrode active material component, and coats it with binder and optional conductive agent on the surface of the current collector. This can give full play to the advantages of the silicon-carbon material in terms of high specific capacity, low volume expansion and high structural stability, and improve the overall energy density and cycle durability of the negative electrode sheet.

[0038] The lithium-ion battery provided by the present invention uses the negative electrode sheet prepared by the aforementioned silicon-carbon negative electrode material as the negative electrode, and is assembled with conventional positive electrode, separator and electrolyte. It can effectively give full play to the comprehensive advantages of the negative electrode material of the present invention, such as high specific capacity, high first-cycle coulombic efficiency, low charge and discharge volume expansion and long cycle life, thereby improving the overall energy density, cycle stability and safety and reliability of the battery. Attached Figure Description

[0039] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0040] Figure 1 This is a flowchart illustrating the overall preparation process of the silicon-carbon anode material of this invention. Figure 2 This is a schematic diagram of the microstructure of the negative electrode active material provided in Embodiment 1 of the present invention; Figure 3 The graph shows a comparison of the capacity retention and full-charge expansion performance of the embodiment and the comparative material provided in Experimental Example 1 of this invention after 100 cycles. Detailed Implementation

[0041] The technical solution of the present invention will be clearly and completely described below with reference to the embodiments. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.

[0042] According to one aspect of the present invention, a silicon-carbon anode material comprises a porous carbon framework and silicon deposited on the surface of the open-pore structure channels inside the porous carbon framework, wherein the anode material simultaneously satisfies the following parameter conditions: (a) Microporosity (V) mciro ≥10%, where the microporosity refers to the percentage of the volume of micropores with a pore size of less than 2 nm in the total pore volume of the negative electrode material; (b) The bounded scale ratio Z satisfies 0.2 < Z < 15, where Z = D si / D p D Si D represents the average particle size of the active silicon region. p The average pore size of the porous carbon framework channels; (C) The silicon is introduced by a chemical vapor deposition process, and the deposition temperature of the chemical vapor deposition is 380℃~800℃; (d) The silicon precursor deposition conversion rate Y < 0.1, where Y = (moles of silicon precursor raw material gas / moles of porous carbon framework) / deposition time, and the moles of porous carbon framework are calculated in terms of moles of carbon elements; (e) Silicon precursor utilization rate X(Si) > 92%, where X(Si) = 100 × (number of moles of silicon in the composite) / (total number of moles of silicon precursor feed).

[0043] The silicon-carbon anode material provided by this invention, by limiting the microporosity to ≥10%, ensures that the silicon precursor can fully penetrate into the internal pores of the porous carbon framework, achieving uniform nucleation and confined deposition of silicon on the inner surface of the pore walls, avoiding surface crusting and internal pore vacancy; by limiting the confinement scale ratio Z to the range of 0.2 < Z < 15, the size of the active silicon region and the pore size are geometrically matched, preventing both uncontrolled expansion caused by silicon distributed in discrete particle form and pore blockage caused by cross-pore bridging; and by controlling the chemical vapor deposition temperature at 38°C... Within the temperature range of 0℃ to 800℃, while ensuring sufficient pyrolysis of the silicon precursor, silicon crystallization and carbon framework embrittlement are effectively suppressed, maintaining the isotropic buffering capacity of amorphous silicon. By controlling the silicon precursor deposition conversion rate Y < 0.1, the chemical vapor deposition process is made dominant, suppressing the chemical vapor infiltration effect, thereby maintaining full pore connectivity and improving ion and electron transport efficiency. By ensuring the silicon precursor utilization rate X(Si) > 92%, raw material waste and tail gas treatment burden are significantly reduced while ensuring high silicon loading, improving process economy and safety. The synergistic effect of the above five parameters enables this silicon-carbon anode material to possess high specific capacity, high first-cycle coulombic efficiency, low charge-discharge volume expansion, and long cycle life.

[0044] It should be noted that the parameters (a) to (e) mentioned above in this application are not independent limitations, but rather synergistic and coupled to jointly construct a silicon-carbon composite structure with high silicon content and high stability. The specific analysis and evidence of the effectiveness of each parameter are as follows: (1) Microporosity V micro ≥10%.

[0045] Physical significance of parameters: Micropores (pore size less than 2nm) are the core channels for silicon precursor gas to penetrate into the interior of the carbon skeleton. The microporosity directly determines the number of nucleation sites and the degree of pore availability inside the carbon skeleton, and is the structural basis for realizing confined deposition inside silicon.

[0046] Limitation criteria: When the microporosity is greater than or equal to 10%, the carbon framework has sufficient micropore channels and high-density nucleation sites, allowing the silicon precursor to penetrate into the pores quickly and uniformly, preferentially nucleating and growing on the pore walls to achieve uniform deposition from the inside out, effectively utilizing the internal buffer pores; if the microporosity is too low, the material pores are mainly mesopores and macropores, and the silicon precursor cannot penetrate into the interior, but can only be deposited by cracking at the particle pore openings and outer surfaces.

[0047] Out-of-bounds failure mechanism: When V micro When the efficiency is less than 10%, micropore channels are scarce, and the silicon precursor rapidly decomposes and forms a shell at the pore opening, directly blocking the pore channels. This results in a large number of vacant pores inside and extremely low utilization. At the same time, the surface silicon shell has no structural buffer and is very easy to peel off during charging and discharging, causing a significant decrease in the first-cycle coulombic efficiency and a rapid decay of the cycle capacity.

[0048] (2) Deposition temperature: 380℃~800℃.

[0049] Physical significance of the parameter: Deposition temperature is the core process parameter for controlling the cracking rate of silicon precursor, silicon phase structure and mechanical properties of carbon skeleton, and directly determines the morphology, crystallization state and composite structure stability of deposited silicon.

[0050] The limiting criteria are as follows: 380℃ is the critical temperature for the effective pyrolysis of silane precursors. Temperatures above this level can ensure that the precursors are fully pyrolyzed, meeting the kinetic requirements for high silicon content deposition. 800℃ is the critical crystallization temperature for amorphous silicon. Temperatures below this level can stably maintain the amorphous structure of silicon while avoiding high-temperature damage to the flexibility and toughness of the carbon skeleton.

[0051] Out-of-boundary failure mechanism: When the temperature is below 380℃, the silicon precursor has an extremely low decomposition rate and poor deposition efficiency, making it impossible to achieve high silicon content loading within the conventional process time. In addition, the silicon deposition is uneven and has poor adhesion. When the temperature is above 800℃, the deposited silicon transforms from an amorphous phase to crystalline silicon, losing its isotropic buffering capacity for volume expansion. At the same time, the carbon skeleton becomes excessively graphitized, and its mechanical flexibility decreases. During charging and discharging, structural collapse is likely to occur, leading to material pulverization failure.

[0052] (3) Y < 0.1.

[0053] Physical significance of the parameter: It characterizes the deposition conversion rate of silicon precursor gas into silicon, thus avoiding channel blockage problems from the process level.

[0054] The limitation is based on the fact that CVD technology can achieve uniform deposition from the inside out of the pores, strictly limit the deposition conversion rate of silicon precursor gas into silicon, and can maximize the preservation of pore connectivity, ensuring deposition uniformity and ion transport efficiency.

[0055] Out-of-boundary failure mechanism: When Y is not less than 0.1, the silicon deposition conversion rate is too fast. Silicon preferentially accumulates and deposits at the pore opening, quickly blocking the pore channels. This results in the internal pores not being filled, ion transport being blocked, material polarization increasing, the irreversible capacity of the first cycle increasing, and structural stability decreasing significantly during cycling.

[0056] (4) X(Si) > 92%.

[0057] Physical significance of the parameter: It characterizes the degree of utilization of silicon precursor (silicon precursor utilization rate), which is a core process indicator for raw material cost and process safety. High utilization rate means that silicon precursor is fully converted into product silicon, achieving high silicon loading in confined pores, which in turn determines the upper limit of the specific capacity of the anode material and is a key indicator for achieving high-capacity silicon-carbon anodes.

[0058] Limitation basis: The utilization rate of silicon precursor in traditional processes is relatively low, and a large amount of unreacted silicon precursor is directly discharged, which not only causes raw material waste and increases costs, but also brings safety and environmental protection risks; setting the lower limit of silicon precursor utilization rate to 92%, which is significantly higher than the common level of about 50% in the industry, can greatly reduce raw material costs and exhaust gas treatment burdens. Meanwhile, relying on the structure and process confinement advantages of the present invention, structural stability can still be maintained under high utilization rate and high silicon loading, realizing the compatibility of high capacity and high stability. The measurement of X(Si) adopts thermogravimetric analysis (TGA) to determine the silicon content in the composite and combines with feeding metering: the sample is heated from 25°C to 1100°C in an air atmosphere, all carbon is burned out, and silicon is oxidized to SiO₂, according to the silicon mass = M 1100 ×28 / 60 to calculate the number of moles of silicon (M 1100 is the mass of the sample at 1100°C), then divided by the total number of moles of silicon precursor fed during the reaction and multiplied by 100%; this measurement method is consistent with the general specifications for the characterization of silicon content of silicon-carbon composite materials and silicon precursor utilization, and the results are reproducible and verifiable.

[0059] Out-of-bounds failure mechanism: When X(Si) is not greater than 92%, the utilization rate of silicon precursor is relatively low, and a large amount of silicon precursor is discharged without full reaction. On the one hand, raw material is wasted and cost rises; on the other hand, the silicon loading of the product is insufficient under the same feeding amount, and the proportion of carbon material is relatively too high, which greatly reduces the overall specific capacity of the material. In addition, the increased concentration of residual silicon precursor in the tail gas brings safety and environmental protection risks, which cannot meet the application requirements of high energy density lithium batteries.

[0060] (5), 0.2<Z<15.

[0061] Physical meaning of the parameter: Z=D Si / D p A single dimensionless number is used to characterize the geometric matching relationship between the size of the active silicon region and the pore size of the porous carbon skeleton. D Si is the average particle size of the active silicon region (that is, the equivalent average diameter of the silicon region confined by the pores of the carbon skeleton), D p is the average pore size of the pores of the porous carbon skeleton. Limitation basis: Limiting Z to 0.2<Z<15 can keep a reasonable match between the size of the active silicon region and the average pore size of the pores.

[0062] Out-of-bounds failure mechanism: When Z≤0.2, the size of the active silicon region is much smaller than the pore size, and silicon is scattered in the macropores in the form of discrete nanoparticles, which cannot form a continuous confined filling body. A large number of voids inside the pores are not effectively utilized, and the discrete particles expand independently during charge and discharge without the constraint of the pore wall, resulting in uncontrolled volume expansion and easy pulverization; when Z≥15, the size of the silicon region exceeds the pore scale, and the deposited silicon forms cross-pore bridges at the pore openings, quickly blocking the pores, so that the internal pores cannot be filled continuously, ion transport is hindered, the first-cycle irreversible capacity increases, and the cycle stability decreases.

[0063] In a preferred embodiment of the present invention, the microporosity (V) mciro The percentage is 40% to 95%; And / or, the preferred value range of Z is 0.5 < Z < 0.8.

[0064] In a preferred embodiment, the present invention further limits the microporosity to 40%~95%, which can significantly improve the density and connectivity of micropore channels inside the porous carbon framework, enhance the penetration depth and the number of nucleation sites of the silicon precursor, thereby making fuller use of the internal pore space and improving the uniformity and porosity utilization of silicon deposition. At the same time, the confinement scale ratio Z is further limited to 0.5 < Z < 0.8, so that the size of the active silicon region and the average pore diameter of the channel achieve a better geometric matching state, which is conducive to the formation of a continuous, close-fitting, stress-free confined filling structure of silicon in the channel, further suppressing the volume expansion during the charging and discharging process, and improving the structural stability and cycle reliability of the material.

[0065] In a preferred embodiment of the present invention, the porous carbon skeleton has a specific surface area of ​​300~2500m² / g and a total pore volume of 0.3~2.0cm³ / g.

[0066] And / or, the raw materials for preparing the porous carbon framework are selected from one or more of asphalt, resin, coal, biomass, metal-organic framework compounds and their derivatives; And / or, the D50 particle size of the porous carbon framework is 1 μm to 30 μm.

[0067] In a preferred embodiment, the present invention limits the specific surface area of ​​the porous carbon framework to 300~2500 m² / g and the total pore volume to 0.3~2.0 cm³ / g, which can balance sufficient active site density and effective ion transport channels. This ensures sufficient adsorption and reaction space for the silicon precursor while avoiding the increase of side reactions due to excessively high specific surface area or the weakening of structural support capacity due to excessively large pore volume. The raw materials for preparing the porous carbon framework are selected from one or more of pitch, resin, coal, biomass, metal-organic framework compounds and their derivatives, which is beneficial to control the pore structure characteristics, surface chemical properties and mechanical flexibility of the carbon framework to adapt to the confined deposition requirements under different process conditions. Limiting the D50 particle size of the porous carbon framework to 1μm~30μm can ensure the uniformity of slurry coating and electrode compaction density while taking into account the internal mass transfer efficiency of particles and the mechanical integrity of the overall electrode.

[0068] In a preferred embodiment of the present invention, the silicon is attached to the inner surface of the pore wall of the porous carbon skeleton in the form of a continuous thin film, and the thin film is located inside the pores of the porous carbon skeleton.

[0069] In a preferred embodiment, the silicon of the present invention is attached to the inner surface of the pore wall of the porous carbon skeleton in the form of a continuous thin film and is located in the internal channels. This allows the volume expansion of silicon during charging and discharging to be constrained by the pore wall in all directions, effectively suppressing the pulverization and detachment of active materials and enhancing the interfacial contact stability between silicon and the carbon skeleton.

[0070] Preferably, the thickness of the film is 1 nm to 20 nm.

[0071] In a preferred embodiment of the present invention, the outer surface of the porous carbon skeleton is further covered with a coating layer.

[0072] In a preferred embodiment, the present invention provides a coating layer on the outer surface of a porous carbon skeleton, which can guide the formation of a uniform and stable solid electrolyte interface (SEI) film during the first charge and discharge cycle of the electrode, thereby inhibiting the continuous decomposition of the electrolyte and the loss of active lithium. The coating layer thickness is controlled within the range of 1~50nm, which can effectively cover surface defects and enhance structural integrity, while avoiding excessive thickness that would increase ion transport resistance.

[0073] Preferably, the thickness of the coating layer is 1~50 nm; Preferably, the coating layer is a carbon coating layer or a non-carbon coating layer, wherein the carbon coating layer is an amorphous carbon layer, a graphitized carbon layer, or a composite layer of both, and the non-carbon coating layer is a silicon oxide, a metal oxide, or a polymer.

[0074] According to one aspect of the present invention, a method for preparing the above-mentioned silicon-carbon anode material includes the following steps: (A) Provide a porous carbon framework with a microporosity of ≥10%, and then place the porous carbon framework in a closed reactor and introduce a mixture of silicon precursor gas. (B) At a deposition temperature of 380–800 °C, silicon is uniformly deposited in the pores of a porous carbon framework by chemical vapor deposition (CVD) process. The proportion of chemical vapor infiltration process is strictly controlled so that the resulting anode material satisfies Y < 0.1, X(Si) > 92%, and 0.2 < Z < 15.

[0075] The method for preparing silicon-carbon anode materials provided by this invention involves step (A) selecting a porous carbon framework with a microporosity ≥10% and introducing a mixed gas containing silicon precursors to provide necessary permeation channels and nucleation basis for the silicon precursors to penetrate deep into the pores; and step (B) implementing a deposition process dominated by chemical vapor deposition within a precise temperature window of 380–800°C, while strictly controlling the proportion of chemical vapor permeation. This simultaneously achieves efficient pyrolysis of the silicon precursors, uniform and continuous silicon film formation on the inner surface of the pore walls, and the synergistic achievement of high silicon precursor utilization and confinement size ratio. Thus, from the source of the process, the resulting silicon-carbon anode material is guaranteed to have comprehensive performance characteristics such as high silicon loading, low volume expansion, high first-cycle coulombic efficiency, and long-cycle stability.

[0076] In a preferred embodiment of the present invention, the silicon-containing precursor mixed gas in (A) is formed by mixing the silicon-containing precursor with a carrier gas; Preferably, the silicon-containing precursor is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; Preferably, the carrier gas is an inert gas; Preferably, the volume fraction of the silicon-containing precursor in the silicon-containing precursor mixture is 5% to 50%, and the system pressure is 5 to 50 kPa.

[0077] In a preferred embodiment of the present invention, the chemical vapor deposition in (B) is a segmented temperature-controlled deposition: The temperature for the pre-deposition stage is 380~450℃ and the time is 0.2~0.5 h, while the temperature for the main deposition stage is 450~800℃ and the time is 1.0~2.5 h.

[0078] Figure 1 This is a flowchart illustrating the overall preparation process of the silicon-carbon anode material of this invention.

[0079] See Figure 1 It can be seen that the overall preparation method of the silicon-carbon anode material in this application includes: S1: Provides a porous carbon framework.

[0080] Porous carbon frameworks were prepared by selecting one or more of the following raw materials: asphalt, resin, coal, biomass, metal-organic frameworks (MOFs) and their derivatives. The pore structure was controlled by physical or chemical activation methods to ensure the predetermined microporosity V of the obtained porous carbon framework. micro ≥10% (i.e., the volume percentage of micropores with a pore size of less than 2nm in the total pore volume of the negative electrode material is ≥10%).

[0081] S2: Placed in a closed reactor.

[0082] The porous carbon framework obtained in step S1 is loaded into a closed reactor, the reactor is sealed, and an inert gas is introduced for purging to displace the internal air, so as to provide an inert gas protection environment. At the same time, the system pressure is regulated and maintained within a preset range (e.g., 5~50 kPa).

[0083] S3: Introduce a silicon-containing precursor mixed gas.

[0084] The silicon-containing precursor mixed gas is introduced into the closed reactor. Wherein, the silicon-containing precursor is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; the carrier gas is an inert gas (e.g., argon, nitrogen, etc.). A mass flow controller is used to precisely regulate the ratio of the precursor to the carrier gas and the total flow rate, so that the volume fraction of the silicon-containing precursor in the mixed gas is maintained within a preset range.

[0085] S4: Segmented temperature-controlled chemical vapor deposition.

[0086] The heating system is turned on to perform segmented temperature-controlled chemical vapor deposition on the reactor. The deposition temperature is strictly controlled within a specific window of 380°C to 800°C, which specifically includes a pre-deposition stage and a main deposition stage. Throughout the entire deposition process, the feed rate of the silicon precursor and the deposition time are precisely controlled, so that the deposition conversion rate Y of the silicon precursor satisfies Y<0.1.

[0087] S5: Silicon is confined and deposited inside the pores.

[0088] During the deposition process in step S4, the active silicon species generated by the cracking of the silicon precursor penetrate into the pores of the open pore structure inside the porous carbon framework, and nucleate and grow uniformly along the pore walls to form a continuously adhered amorphous thin film. The equivalent thickness of the thin film is controlled to be 1 nm to 20 nm, and the confinement scale ratio Z is strictly limited to satisfy 0.2<Z<15, so as to realize geometric adaptation and confined filling of silicon in the pores.

[0089] S6: (Optional scheme) Coating the outer surface with a carbon layer.

[0090] According to actual application requirements, the confined deposition product obtained in step S5 can be optionally subjected to outer surface coating treatment. A carbon coating layer with a thickness of 1 nm to 50 nm is formed on the outer surface of the porous carbon framework, so as to improve the surface conductivity and structural stability of the material.

[0091] This step is an optional step, and can be omitted if coating is not required.

[0092] S7: Obtain the silicon-carbon anode material.

[0093] After the deposition is finished, stop heating and allow the reactor to cool naturally to room temperature, then stop the gas introduction and take out the product. After post-treatment processes such as sieving and drying, the target silicon-carbon anode material is finally obtained. This material needs to simultaneously satisfy the following parameter conditions: microporosity Vmicro ≥10%, 0.2<Z<15, Y<0.1, and silicon precursor utilization X(Si)>92%. The obtained material has excellent electrochemical properties combining high initial coulombic efficiency, low volume expansion and long cycle life.

[0094] According to one aspect of the present invention, a negative electrode sheet for a lithium ion battery is provided, the negative electrode sheet comprises a current collector and a negative active material layer coated on the surface of the current collector, and the negative active material layer comprises the above-mentioned silicon-carbon negative electrode material, a binder and an optional conductive agent; For the negative electrode sheet for lithium ion battery provided by the present invention, the silicon-carbon negative electrode material is used as the negative active material component, combined with the binder and optional conductive agent to coat on the surface of the current collector, which can fully exert the advantages of the silicon-carbon material in high specific capacity, low volume expansion and high structural stability, and improve the overall energy density and cycle durability of the negative electrode sheet.

[0095] Preferably, the mass proportion of the silicon-carbon negative electrode material in the negative active material layer is 3% to 100%.

[0096] According to one aspect of the present invention, a lithium ion battery is provided, the lithium ion battery comprises a positive electrode, a negative electrode, a separator and an electrolyte, and the negative electrode is the above-mentioned negative electrode sheet for lithium ion battery of the present invention.

[0097] The lithium ion battery provided by the present invention is assembled by using the negative electrode sheet prepared from the aforementioned silicon-carbon negative electrode material of the present invention as the negative electrode, in combination with a conventional positive electrode, separator and electrolyte, which can effectively exert the comprehensive advantages of the negative electrode material of the present invention in high specific capacity, high initial coulombic efficiency, low charge-discharge volume expansion and long cycle life, thereby improving the overall energy density, cycle stability, safety and reliability of the battery.

[0098] The technical solution of the present invention will be further described below with reference to the examples.

[0099] Example 1 A preparation method of a silicon-carbon negative electrode material comprises the following steps: S1: Providing a porous carbon skeleton.

[0100] Pitch is selected as the raw material, and the porous carbon skeleton is prepared by a physical activation method. Upon testing, the porous carbon skeleton has a BET specific surface area of 1500 m² / g, a total pore volume of 1.2 cm³ / g, and a preset microporosity V micro of 18% (that is, the volume percentage of the micropore volume with a pore size of less than 2 nm in the total pore volume of the negative electrode material is 18%).

[0101] S2: Placing the porous carbon skeleton in a closed reactor.

[0102] Load the porous carbon framework prepared above into a closed chemical vapor deposition (CVD) reactor, seal the reactor, and perform repeated purging by introducing high-purity argon to displace the internal air and provide an inert gas protection environment. Adjust and maintain the system pressure at 10 kPa.

[0103] S3. Introduce a silicon-containing precursor mixed gas.

[0104] Introduce the silicon-containing precursor mixed gas into the closed reactor. The silicon-containing precursor is silane (SiH₄), and the carrier gas is high-purity argon (Ar). Through precise regulation by a mass flow controller, the volume fraction of silane in the mixed gas is 10%, and the gas is kept introduced continuously and stably.

[0105] S4. Perform segmented temperature-controlled chemical vapor deposition.

[0106] Turn on the heating system to carry out segmented temperature-controlled chemical vapor deposition on the reactor. The specific process is as follows: first perform pre-deposition at 450°C for 0.3 h, then raise the temperature to 600°C for main deposition for 1.8 h. Throughout the entire deposition process, the feed rate of the silicon precursor is precisely controlled. It is calculated that the deposition conversion rate Y of the silicon precursor is 0.03 (where Y = (moles of silicon precursor raw gas / moles of porous carbon framework) / deposition time, and the moles of the porous carbon framework are calculated based on the moles of carbon element), ensuring that the deposition process is absolutely dominated by the CVD process.

[0107] S5. Perform confined deposition of silicon inside the pores.

[0108] Under the temperature control and gas introduction conditions in step S4, the active silicon species generated by silane pyrolysis penetrate into the internal pores of the porous carbon framework, and nucleate and grow uniformly along the pore walls, forming a continuously fitted amorphous thin film. Characterized by transmission electron microscopy (TEM), the equivalent thickness of the thin film is 1.0 nm to 15 nm (about 1.5 to 5 nm on average), and the average particle size D of the active silicon region Si and the average pore diameter D of the pores of the porous carbon framework p the ratio (i.e., the confined scale ratio Z) satisfies 0.2<Z<15, realizing the confined filling of silicon inside the pores, and the crystallinity of amorphous silicon is relatively low.

[0109] S6. Coat the outer surface with a carbon layer.

[0110] After the deposition is completed, stop heating and continue to introduce argon until the reactor naturally cools to room temperature. Subsequently, a CVD method is used to coat an amorphous carbon layer on the outer surface of the obtained confined deposition product, and the thickness of the coating layer is controlled to 10 nm, so as to improve the surface conductivity and structural stability of the material.

[0111] S7. Obtain the silicon-carbon negative electrode material.

[0112] The product obtained in step S6 is taken out and subjected to post-processing steps such as sieving and vacuum drying to finally obtain the target silicon-carbon anode material.

[0113] Figure 2 This is a schematic diagram of the microstructure of the negative electrode active material provided in Embodiment 1 of the present invention; Depend on Figure 2 As can be seen, in the silicon-carbon anode material obtained in Example 1 of the present invention, silicon is attached to the pore wall of the porous carbon skeleton in the form of a continuous / semi-continuous and uniform amorphous film, without obvious surface crust or discrete particle accumulation; the size of the active silicon region matches the pore size well, intuitively presenting the geometric adaptation characteristics characterized by the confinement scale ratio Z, which confirms the effectiveness of the confinement deposition structure of the present invention.

[0114] Example 2 A method for preparing a silicon-carbon anode material includes the following steps: S1 provides a porous carbon framework.

[0115] A porous carbon framework was prepared by using resin as a raw material and an activation method. The BET specific surface area of ​​this porous carbon framework was tested to be 1800 m² / g, and the microporosity V0.05 was [not specified]. micro It is 12%.

[0116] S2, Placed in a closed reactor: Same as in Example 1.

[0117] S3. Introduce a mixture of gases containing silicon precursors.

[0118] A silicon precursor mixture is introduced into a closed reactor. The silicon precursor is silane (SiH4), and the carrier gas is nitrogen (N2). The volume fraction of silane in the mixture is precisely controlled using a mass flow controller to maintain an 8% volume fraction and a system pressure of 5 kPa, while ensuring a continuous and stable gas flow.

[0119] S4, isothermal chemical vapor deposition.

[0120] The heating system was turned on to perform isothermal chemical vapor deposition in the reactor. The specific process involved isothermal deposition at 450℃ for 2.5 hours. Throughout the deposition process, the feed rate of the silicon precursor was precisely controlled, and the calculated silicon precursor deposition conversion rate Y was 0.05.

[0121] S5, silicon is deposited within the pores.

[0122] Under the temperature and ventilation conditions of step S4, the active silicon species generated by silane pyrolysis penetrate deep into the internal pores of the porous carbon framework and nucleate and grow uniformly along the pore walls, forming a continuous and adherent amorphous film, thus achieving confined filling of silicon within the pores. Raman spectroscopy characterization showed that the crystallinity I of the obtained silicon was... c-Si / Ia-Si The value is 0.18, confirming that it is an amorphous form.

[0123] S6. Carbon coating on the outer surface: Same as in Example 1.

[0124] S7. Silicon-carbon anode material is obtained.

[0125] The product obtained in step S6 is taken out and subjected to post-processing steps such as sieving and vacuum drying to finally obtain the target silicon-carbon anode material.

[0126] Example 3 A method for preparing a silicon-carbon anode material includes the following steps: S1. Provides a porous carbon framework: A porous carbon framework was prepared by carbonization activation using metal-organic frameworks (MOFs) as precursors. The BET specific surface area of ​​this porous carbon framework was measured to be 2200 m² / g, and the microporosity V0.05 was [not specified in the original text]. micro It is 85%.

[0127] S2, Placed in a closed reactor: Same as in Example 1.

[0128] S3. Introduce a mixed gas containing silicon precursor: A silicon precursor mixture is introduced into a closed reactor. The silicon precursor is silane (SiH4), and the carrier gas is high-purity argon (Ar). The volume fraction of silane in the mixture is precisely controlled to be 15% using a mass flow controller, and the system pressure is controlled to be 20 kPa, while maintaining a continuous and stable gas flow.

[0129] S4. Segmented temperature-controlled chemical vapor deposition: The heating system was activated, and segmented temperature-controlled chemical vapor deposition was performed in the reactor. The specific process was as follows: first, pre-deposition was carried out at 400℃ for 0.2 h, followed by main deposition at 550℃ for 2.0 h. Throughout the deposition process, the feed rate of the silicon precursor was precisely controlled; the calculated silicon precursor deposition conversion rate Y was 0.02.

[0130] S5, Silicon is confined and deposited inside the pores: Under the temperature and ventilation conditions of step S4, the active silicon species generated by silane pyrolysis penetrate deep into the internal pores of the porous carbon framework and nucleate and grow uniformly along the pore walls, forming a continuous and adherent amorphous film, thus achieving confined filling of silicon within the pores. Raman spectroscopy characterization showed that the crystallinity I of the obtained silicon was... c-Si / I a-Si The value is 0.09, confirming that it is an amorphous form.

[0131] S6. Carbon coating on the outer surface: Same as in Example 1.

[0132] S7. Obtain silicon-carbon anode material: The product obtained in step S6 is taken out and subjected to post-processing steps such as sieving and vacuum drying to finally obtain the target silicon-carbon anode material.

[0133] Example 4 In this embodiment, except for the microporosity V of the porous carbon framework in step S1 micro Except for the 10% BET specific surface area, 1200 m² / g, and total pore volume of 0.8 cm³ / g, the rest are the same as in Example 1.

[0134] Example 5 Except for step S1, where the porous carbon framework uses MOF-derived carbon, the microporosity Vmicro is 95%, the BET specific surface area is 2500 m² / g, and the total pore volume is 1.8 cm³ / g, and step S3, where the silane volume fraction is 15% and the system pressure is 20 kPa, and step S4, where the deposition process is 400℃ pre-deposition for 0.2 h and 550℃ main deposition for 2.0 h, the rest of this embodiment is the same as in Example 1.

[0135] Example 6 Except for step S4, where the deposition process is constant temperature deposition at 380℃ for 3.0h, the rest of this embodiment is the same as in embodiment 1.

[0136] Example 7 Except for step S3, where the silane volume fraction is 5% and the system pressure is 30 kPa, and step S4, where the deposition process is 500℃ pre-deposition for 0.5 h and 800℃ main deposition for 1.0 h, the rest of this embodiment is the same as in embodiment 1.

[0137] Example 8 In this embodiment, except for step S1 where the porous carbon framework is made of resin, has a BET specific surface area of ​​2000 m² / g, and a microporosity of V, the following features are also present. micro The content is 60%, the volume fraction of silane in step S3 is 8%, the system pressure is 5 kPa, and the deposition process in step S4 is constant temperature deposition at 450℃ for 2.5h, the rest is the same as in Example 1.

[0138] Example 9 In this embodiment, except for the metal-organic framework (MOF) derived carbon used as the porous carbon framework precursor in step S1, the microporosity V micro The silane volume fraction was 50%, the BET specific surface area was 2000 m² / g, the total pore volume was 1.5 cm / g, and the silane volume fraction in step S3 was 15%, the system pressure was 20 kPa, and the deposition process in step S4 was pre-deposition at 450℃ for 0.3 h and main deposition at 600℃ for 1.8 h. Except for the confinement scale ratio Z, which was characterized by transmission electron microscopy as being approximately 13, the rest was the same as in Example 1.

[0139] This embodiment is used to verify that when the confinement scale ratio Z is near the upper limit of 15, the technical solution of the present invention can still achieve excellent and stable confinement deposition effect.

[0140] Comparative Example 1 In this comparative example, the microporosity V of the porous carbon framework in step S1 is excluded. micro Except for the 5% BET specific surface area, 800 m² / g, and total pore volume of 0.5 cm³ / g, the rest are the same as in Example 1.

[0141] Comparative Example 2 The difference between this comparative example and Example 1 is that the "segmented temperature-controlled chemical vapor deposition" in step S4 of Example 1 is replaced with "750℃ isothermal deposition for 1.8h".

[0142] Except for step S4, where the deposition process is constant temperature deposition at 750℃ for 1.8 hours, the comparative example is the same as Example 1.

[0143] Comparative Example 3 Except for step S4, where the silicon precursor deposition conversion rate Y is increased by increasing the silane feed flow rate and shortening the deposition time to achieve a value of 0.4, this comparative example is identical to Example 2.

[0144] The measured silicon precursor utilization rate X(Si) of this comparative example is 93%. However, the orifice blockage and cycle performance deterioration are caused by Y=0.4 exceeding the upper limit of 0.1. Therefore, the necessity of limiting the Y parameter is verified separately.

[0145] Comparative Example 4 Except for step S4, in which the main deposition time is shortened to 0.5 h to achieve a silicon precursor utilization rate X(Si) of 82%, this comparative example is the same as Example 3.

[0146] Comparative Example 5 Except for step S4, where the average particle size of the active silicon region is increased by increasing the deposition temperature and extending the deposition time, and the confinement size ratio Z is approximately 20 as characterized by transmission electron microscopy, the rest of this comparative example is the same as in Example 3.

[0147] This embodiment is used to verify that when Z exceeds the upper limit of 15, the silicon region size exceeds the channel size, cross-channel bridging and orifice blockage occur, resulting in significant deterioration of cycle performance and volume expansion.

[0148] Experimental Example 1 Using the silicon-carbon anode materials obtained in Examples 1-9 and Comparative Examples 1-5 as anode active materials, anode sheets were prepared respectively. The anode sheets were used to prepare CR2032 coin cells using conventional methods, and the electrical performance of the cells was tested.

[0149] The specific method is as follows: (1) Half-cell assembly: Assemble CR2032 button cells in a glove box, with lithium metal sheet as counter electrode, polypropylene microporous membrane as separator, and LiPF6 dissolved in a mixture of ethyl carbonate (EC) and diethyl carbonate (DEC) (volume ratio EC:DEC=1:1), wherein the concentration of LiPF6 is 1mol / L.

[0150] The battery was tested for charge and discharge using the LAND battery testing system.

[0151] (2) Cyclic specific capacity and initial efficiency test: After the CR2032 button cell was left to stand for 6 hours, it was discharged at 0.1C to 0.005V and the capacity was recorded as Q1; then it was discharged at a constant voltage of 0.005V until the current was cut off at 0.01C and the total capacity was recorded as Q2; after standing for 5 minutes, it was charged at a constant current of 0.1C to 1.5V; the initial delithiation specific capacity is the specific capacity (or mass specific capacity) of the electrode material, and the ratio of the initial delithiation capacity to the initial lithium insertion capacity is the initial coulombic efficiency of the battery.

[0152] (3) Capacity retention rate test: After standing for 5 minutes, repeat the above charge and discharge steps twice; then discharge to 0.005V at 0.25C; after standing for 5 minutes, charge to 1.5V at a constant current of 0.25C, and cycle 50 times. The capacity retention rate is calculated by dividing the specific capacity of the 50th cycle by the charging capacity of the 1st cycle by 100%.

[0153] The test results are shown in Tables 1 and 2.

[0154] Table 1. Parameter results of silicon-carbon anode materials in each embodiment and comparative example:

[0155] Table 2 Performance results of each embodiment and comparative example:

[0156] As shown in Tables 1 and 2 above, Examples 1 to 9 of the present invention simultaneously satisfy five parameters: microporosity ≥10%, 0.2 < Z < 15, deposition temperature 380℃~800℃, Y < 0.1, and X(Si) > 92%. The first-cycle coulombic efficiency is 82%~88%, the capacity retention rate after 100 cycles is ≥90%, and the full-charge expansion rate is ≤68%, exhibiting the synergistic advantages of high specific capacity, high first-cycle efficiency, and low expansion.

[0157] Comparative Example 1 due to microporosity V micro=5% (<10%) leads to a lack of micropore channels and shelling and blockage of silicon precursor pores, resulting in a sharp drop in capacity retention to 58% and a rise in full-charge expansion to 85%; Comparative Example 2 uses isothermal deposition at 750℃ to crystallize silicon, resulting in a drop in capacity retention to 68% and a rise in full-charge expansion to 71%; Comparative Example 3, due to Y=0.4 (>0.1), results in chemical vapor infiltration dominating and preferential pore blockage, resulting in a drop in capacity retention to 63%; Comparative Example 4, due to insufficient silicon loading of X(Si)=82% (<92%), results in a sharp drop in specific capacity to 1108 mAh / g; Comparative Example 5, due to Z=20 (>15), results in transpore bridging, and a rise in full-charge expansion to 95%.

[0158] The above results show that, in embodiments outside the range of the five performance parameters of the present invention—microporosity, confinement size ratio, chemical vapor deposition temperature, silicon precursor deposition conversion rate, and silicon precursor utilization—the electrochemical performance is significantly degraded. This verifies the necessity and effectiveness of the five-parameter synergistic confinement system of the present invention for structural stability and volume expansion suppression under high silicon load.

[0159] Figure 3 The graph shows a comparison of the capacity retention and full-charge expansion performance of the embodiment and the comparative material provided in Experimental Example 1 of this invention after 100 cycles.

[0160] Depend on Figure 3 It can be seen that the capacity retention rate of the materials in each embodiment after 100 cycles is significantly higher than that of the comparative example, and the full charge expansion rate is significantly lower than that of the comparative example. Among them, embodiments 1 to 9 satisfy the five-parameter synergistic system, with a capacity retention rate ≥90% and a full charge expansion rate ≤68%, while the capacity retention rate of comparative examples 1 to 6 drops to 58%~75% and the full charge expansion rate rises to 71%~100%, which directly verifies the regulatory effect of the five core parameter synergistic confinement system of the present invention on cycle stability and volume expansion.

[0161] In summary, this invention constructs a highly stable, high-silicon silicon-carbon composite structure through precise synergistic control of five core parameters: a high-microporosity carbon framework provides ample internal deposition channels and buffer space; a dedicated temperature window stabilizes the amorphous silicon phase, preserving deformation buffering capacity; low Y ensures chemical vapor deposition dominates and pores are fully interconnected; high silane utilization X(Si) enables the silicon precursor to be fully converted into product silicon, achieving high silicon loading within confined pores and providing an ultra-high specific capacity close to elemental silicon. The confinement-to-size ratio ensures a matching between the active silicon region and the pore size, allowing silicon to be fully confined and filled rather than discretely distributed or bridged across pores. The coupling of these five parameters enables the material to achieve low expansion, high initial efficiency, and long cycling even with high silicon content, solving the industry challenge of reconciling high silicon content with high stability.

[0162] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A silicon-carbon anode material, characterized in that, The silicon-carbon anode material comprises a porous carbon framework and silicon deposited on the surface of the open-pore structure channels inside the porous carbon framework. The anode material simultaneously satisfies the following parameter conditions: (a) Microporosity ≥ 10%, whereby microporosity refers to the percentage of the volume of micropores with a diameter of less than 2 nm in the total pore volume of the negative electrode material; (b) The confinement size ratio Z satisfies 0.2 < Z < 15, where Z = Dsi / Dp, Dsi is the average particle size of the active silicon region, and Dp is the average pore size of the porous carbon framework channels. (c) The silicon is introduced by a chemical vapor deposition process, and the deposition temperature of the chemical vapor deposition is 380℃~800℃; (d) The silicon precursor deposition conversion rate Y < 0.1, where Y = (moles of silicon precursor raw material gas / moles of porous carbon framework) / deposition time, and the moles of porous carbon framework are calculated in terms of moles of carbon elements; (e) Silicon precursor utilization rate X(Si) > 92%, where X(Si) = 100 × (number of moles of silicon in the composite) / (total number of moles of silicon precursor feed).

2. The silicon-carbon anode material according to claim 1, characterized in that, The microporosity is 40%~95%; And / or, the preferred value range of Z is 0.5 < Z < 0.

8.

3. The silicon-carbon anode material according to claim 1, characterized in that, The porous carbon framework has a specific surface area of ​​300~2500m² / g and a total pore volume of 0.3~2.0cm³ / g; And / or, the raw materials for preparing the porous carbon framework are selected from one or more of asphalt, resin, coal, biomass, metal-organic framework compounds and their derivatives; And / or, the D50 particle size of the porous carbon framework is 1 μm to 30 μm.

4. The silicon-carbon anode material according to claim 1, characterized in that, The silicon is attached to the inner surface of the pore wall of the porous carbon skeleton in the form of a continuous thin film, and the thin film is located inside the pores of the porous carbon skeleton. And / or, the thickness of the film is 1 nm to 20 nm.

5. The silicon-carbon anode material according to claim 1, characterized in that, The outer surface of the porous carbon skeleton is also covered with a coating layer; And / or, the thickness of the coating layer is 1~50nm; And / or, the coating layer is a carbon coating layer or a non-carbon coating layer, wherein the carbon coating layer is an amorphous carbon layer, a graphitized carbon layer, or a composite layer of both, and the non-carbon coating layer is a silicon oxide, a metal oxide, or a polymer.

6. A method for preparing the silicon-carbon anode material according to any one of claims 1 to 5, characterized in that, Includes the following steps: (A) Provide a porous carbon framework with a microporosity of ≥10%, and then place the porous carbon framework in a closed reactor and introduce a mixture of silicon precursor gas. (B) At a deposition temperature of 380–800 °C, silicon is uniformly deposited in the pores of a porous carbon framework by chemical vapor deposition (CVD) process. The proportion of chemical vapor infiltration process is strictly controlled so that the resulting anode material satisfies Y < 0.1, X(Si) > 92%, and 0.2 < Z < 15. The chemical vapor deposition is a segmented temperature-controlled deposition.

7. The preparation method according to claim 6, characterized in that, The silicon-containing precursor mixed gas in (A) is formed by mixing the silicon-containing precursor with a carrier gas; And / or, the silicon-containing precursor is selected from one or more of silane, dichlorosilane, trichlorosilane, and silicon tetrachloride; And / or, the carrier gas is an inert gas; And / or, the volume fraction of the silicon-containing precursor in the silicon-containing precursor mixture is 5% to 50%, and the system pressure is 5 to 50 kPa.

8. The preparation method according to claim 6, characterized in that, The segmented temperature-controlled deposition in (B) includes a pre-deposition stage and a main deposition stage performed sequentially: The temperature for the pre-deposition stage is 380~450℃ and the time is 0.2~0.5 h, while the temperature for the main deposition stage is 450~800℃ and the time is 1.0~2.5 h.

9. A lithium-ion battery negative electrode sheet, characterized in that, It includes a current collector and a negative electrode active material layer coated on the surface of the current collector, wherein the negative electrode active material layer comprises the silicon-carbon negative electrode material according to any one of claims 1 to 5, a binder, and an optional conductive agent; And / or, the silicon-carbon anode material accounts for 3% to 100% of the mass of the anode active material layer.

10. A lithium-ion battery, characterized in that, It includes a positive electrode, a negative electrode, a separator, and an electrolyte, wherein the negative electrode is the lithium-ion battery negative electrode sheet according to claim 9.